2018
DOI: 10.1186/s13287-018-0801-9
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells in spheroids improve fertility in model animals with damaged endometrium

Abstract: BackgroundAsherman’s syndrome (AS) is one of the gynecological disorders caused by the destruction of the endometrium. For some cases of AS available surgical methods and hormonal therapy are ineffective. Stem cell transplantation may offer a potential alternative for AS cure.MethodsHuman endometrial mesenchymal stem cells (eMSC) organized in spheroids were transplanted in rats with damaged endometrium modeled on AS. Treatment response was defined as pregnancy outcome and litter size.ResultsApplication of eMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 49 publications
(47 reference statements)
3
60
0
2
Order By: Relevance
“…Moreover, MenSCs treatment, along with hormonal stimulation, was shown to improve endometrium structure and fertility potential in women with Asherman syndrome (84). Another study reported that MenSCs treatment increases fertility through induction of angiogenic and antiinflammatory factors in a rat model of Asherman syndrome (85). Other work has found that MenSCs produce functional spheroids, which appear to be essential for their observed therapeutic effects (86).…”
Section: Menstrual Blood-derived Mesenchymal Stem Cells (Menscs)mentioning
confidence: 99%
“…Moreover, MenSCs treatment, along with hormonal stimulation, was shown to improve endometrium structure and fertility potential in women with Asherman syndrome (84). Another study reported that MenSCs treatment increases fertility through induction of angiogenic and antiinflammatory factors in a rat model of Asherman syndrome (85). Other work has found that MenSCs produce functional spheroids, which appear to be essential for their observed therapeutic effects (86).…”
Section: Menstrual Blood-derived Mesenchymal Stem Cells (Menscs)mentioning
confidence: 99%
“…In both experimental models [ 103 , 104 , 105 , 106 , 107 ] and humans [ 108 , 109 , 110 , 111 ] the regeneration of endometrium through a stem cell approach has been evaluated. Mesenchymal, bone-marrow-derived stem cells and menstrual blood-derived stromal cells were investigated in this context.…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…Mesenchymal, bone-marrow-derived stem cells and menstrual blood-derived stromal cells were investigated in this context. For this, distinct methods such as transmyometrial administration to the subendometrial area [ 109 ], direct installation of stromal cells in the uterine cavity after endometrial scratching [ 111 ], and infusion in spiral arterioles through catheters [ 110 ] have been put in application, even stem cells arranged in spheroids for a rat model [ 107 ]. Thus, the first results were not long in coming.…”
Section: Introduction Our Current Knowledge About the Asherman Symentioning
confidence: 99%
“…Moreover, MenSCs treatment, along with hormonal stimulation, was shown to improve endometrium structure and fertility potential in women with Asherman syndrome [ 91 ]. Domnina et al, reported that MenSCs treatment increases fertility through induction of angiogenic and anti-inflammatory factors in a rat model of Asherman syndrome [ 92 ]. Other work has found that MenSCs produce functional spheroids, which appear to be essential for their observed therapeutic effects [ 93 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%